A dedicated illumination system for fatigue crack-growth measurement. (August 2016) - Tavares, Paulo J.; Viriato, Nuno; Vaz, A.P.; Moreira, P.M.G.P.
Graphical abstract: Highlights: Innovative illumination device to assist in the automation of crack-growth analysis. Lighting enhancement enables application of morphological image processing. Results show a good agreement with previous studies using standard techniques. Device can render fatigue tests eight times as fast as the traditional measurements. Device tackles measurement variability due to human error alleviating its impact. Abstract: This letter describes the design and development of a dedicated lighting system for the automation of fatigue crack-growth measurements. Crack growth testing is important to the characterization of the expected behaviour during service. Characteristic da / dN vs. Δ K enables the Mechanical Engineer's understanding of the material state in the presence of stress, and assists in the calculation of the remaining fatigue life expected behaviour. Similar to the darkfield illumination principle, the developed system uses a grazing incidence angle to enhance even the smallest crack detail, a necessary feature to enable the successful application of image processing methodologies for crack-growth monitoring. A poor or wrong illumination fails to reveal the true extent of hairline cracks, greatly influencing calculations that depend on large stress gradients. The device is being used in combination with a vision system for continuous monitoring of crack-growth in metallic specimens with great success. The results obtained to date are in full agreement with the expected data for the utilized specimens, which increases the confidence in the use of the device and the continuous work towards automation of fatigue experimental procedures.